Critical scrutiny of the world of the marriage as a myth of male power - Adawiyah, Robiatul (citeus, 2025)
For centuries, men have been considered the dominant gender, exercising hegemony over women. On the other hand, women have been conceptualized as subordinates who obey the orders of men. However, in reality, all images of male power and domination are just myths, a construction made by society to perpetuate patriarchy. Warren Farrel argues that the concept of male superiority is mistaken, as evidenced by the empirical data he presents, which shows that men have long been subordinate to women. Through the Korean drama The World of The Marriade (TWoTM), this study attempts to examine the myth of male power depicted in TWoTM and the concept of power reflected in TWoTM. This study examines alternative perspectives in the gender discourse, which has traditionally been fixated on women's rights and the feminist movement. Hopefully, this study can contribute to the ongoing evolution of gender studies, encouraging inclusivity in various dimensions and transcending the boundaries of monolithic gender narratives.